Pendapat Siswa tentang Pelaksanaan Instrumen Non-Tes - Melia Sutra Dewi; Indra Ibrahim (Jurnal Konseling dan Pendidikan, 2014)
Implementation of the non-test instrument is essential to support the guidance and counseling services in schools. Phenomenon in the field of guidance and counseling teachers less preparing/planning the implementation of the non-test instrument and there is guidance and counseling teachers who do not deliver the results to the students as well as less use of non-test instrument results . This study aims to describe students' opinions about: (1) preparation/planning, (2) the administration, (3) the delivery of results, and (4) the use of non-test instrument results. Type a descriptive study with a class XI student population numbering 178 people. Samples numbered 61 people were taken using purposive sampling technique. Data were collected using a questionnaire and analyzed by a percentage formula. The results showed that students' opinions on the implementation of the non-test instrument with respect to: (1) preparation/planning done well, (2) the administration, (3) the delivery of results, and (4) the use of non-test results is less instrument performing well.